2003
DOI: 10.1002/ana.10517
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of pallidotomy versus medical therapy for Parkinson's disease

Abstract: Thirty-six patients with Parkinson's disease (PD) were randomized to either medical therapy (N ‫؍‬ 18) or unilateral GPi pallidotomy (N ‫؍‬ 18). The primary outcome variable was the change in total Unified Parkinson's Disease Rating Scale (UPDRS) score at 6 months. Secondary outcome variables included subscores and individual parkinsonian symptoms as determined from the UPDRS. At the six month follow-up, patients receiving pallidotomy had a statistically significant reduction (32% decrease) in the total UPDRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
129
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(146 citation statements)
references
References 40 publications
11
129
1
5
Order By: Relevance
“…Several reports demonstrate that bilateral STN DBS reduces rigidity as measured by clinical ratings in PD patients (Deuschl et (Vitek et al, 2003). However, these previous reports relied on clinical rigidity rating scales and did not employ objective, quantitative measures of rigidity.…”
Section: Control Of Rigiditymentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports demonstrate that bilateral STN DBS reduces rigidity as measured by clinical ratings in PD patients (Deuschl et (Vitek et al, 2003). However, these previous reports relied on clinical rigidity rating scales and did not employ objective, quantitative measures of rigidity.…”
Section: Control Of Rigiditymentioning
confidence: 99%
“…Indeed, by recording from implanted STN DBS electrodes, the STN or nearby structures were shown to be active before self-paced movement in PD patients and such activity was induced by both ipsilateral and contralateral hand movement (Paradiso et al, 2003). This may also be the functional basis for the ipsilateral reduction of bradykinesia and rigidity by unilateral pallidotomy (Vitek et al, 2003). Takakusaki et al, 1996).…”
Section: Control Of Bradykinesiamentioning
confidence: 99%
See 1 more Smart Citation
“…38 Kishore et al 45 initially reported significant benefits at 6 months on all features of PD after unilateral pallidotomy, but by 24 months the only stable effects were on contralateral tremor and drug-induced dyskinesia. 46 In the RCT reported by Vitek et al, 33 the 34% decrease in the motor UPDRS score at 6 months waned to a 25% decrease at 24 months, similar to the 21% decrease found by the Toronto group at 24 months. 47 Whether these results signify a mitigation of the effects of expectation, truly waning clinical effects of pallidotomy, or advancing disease is not easy to assess.…”
Section: 31mentioning
confidence: 52%
“…[32][33][34][35][36] In a prospective single-blind (observer-blind) study without a control group, Lozano et al 34 found a 30% benefit from baseline 'off' period total motor (part 3) scores on the Unified Parkinson's Disease Rating Scale (UPDRS) after unilateral pallidotomy, with blinded videotape evaluations to control for observer bias, whereas Ondo et al 36 found only a 13.6% benefit (Table 1). Recently, two single-blind (observer-blind) RCTs 32,33 comparing unilateral pallidotomy to best medical therapy demonstrated 31% to 34% decrease in 'off' total motor UPDRS scores at 6 months, in contrast to 4% to 8% worsening in the control group.…”
Section: 31mentioning
confidence: 99%